Mechanical properties of the materials for bruxoguards - Lazić, Vojkan (Materiali in tehnologije, 2014)
The aim of this study is to investigate the mechanical properties of polymethyl methacrylate (PMMA) and thermoplastic polycarbonate (TPC) materials in order to produce night bruxoguards. For this purpose we used a static tensile test. In the next step the microstructures of PMMA and TPC were observed. Within this framework special attention was paid to the examination of the tensile-test tube fracture surfaces for both materials. This approach revealed that PMMA is a brittle and TPC is a plastic material. Certain mechanical properties and a review of the crucial areas confirmed that the TPC material is extremely favourable for making occlusal splints.
Keywords: polymers; polimeri; mechanical properties; mehanske lastnosti; characterization; karakterizacija; nočni zobni ščitnik; bruxoguards; polimetil metakrilat; polymethyl methacrylate; termoplastični polikarbonat; thermoplastic polycarbonate